Dabao-kuo and the winning of Mindanao - Magdalena, Federico V. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2009)
This paper argues that the early Japanese presence in Davao had enormous impact on the "winning of Mindanao" as a defining politics in the construction of the Philippine state. Under the American colonial administration (1900-1935), Japanese settlers started coming to Davao on southern Mindanao as early as 1903. Thousands more followed later to open up lands to grow abaca, then a major Philippine export next to sugar. By the 1930s some 25,000 Japanese inhabited that region. Their visible presence gave birth to the monicker, Dabao-kou, meaning "Little Tokyo." Regarded as menacing, the Japanese "colonization" of Davao stirred Filipino nationalism that, in turn, helped shape Philippine territory and hastened the birth of a modern state. During the Commonwealth era, Mindanao became a highly contentious issue in Philippine politics. President Manuel L. Quezon found the Japanese, together with the Moros (Muslims), as convenient scapegoats to rationalize the plan to claim Mindanao as integral to the Philippine territory. Mindanao represents one of the country's three stars symbolized in its flag. Thus, Quezon authorized deployment to this frontier thousands of Christian settlers from Luzon and the Visayas until 1940. Indentured migration resumed more vigorously after World War II, reaching its peak in the 1960s. Consequently, this government project hemmed in the Japanese settlers in Davao, according to the plan. At the same time, it also diluted the Moro population in Mindanao who lived in the adjacent provinces of Cotabato and Lanao. As the politics of Mindanao waxed and waned, the "third star" symbolic of this southern region perfected the Philippine territory. While the Philippines succeeded in resolving the "Japanese menace" it was saddled by issues that would continue to hound the nation today.